ANALISIS FAKTOR INTERNAL DAN LINGKUNGAN KARYAWAN BERKINERJA UNGGUL - Septi Sawandi; M. Syamsul Maarif; Nurmala Katrina Panjaitan (School of Business, Bogor Agricultural University (SB-IPB), 2021)
PT. XYZ facing a mix performance in their sales team, some of sales person giving stelar achievement, some just pass the standard, and others failed. This study aims to describe the profile of salesperson and to analyze the determinants factors of star performers. Methods of data collection using questionnaires, interviews, observation, literature study, and census techniques (64 salesperson). Data analysis using multiple regression. Salesperson who achieved their annual sales target by the late of November were included in star performers category. Salesperson who reached the sales target in December were categorized as achievers, and those who did not reach the annual target were categorized as not achieving. The results showed that most of the salespeople of PT. XYZ is a male (79.69%) having a productive age category 38-47 years (35%), undergraduate education or higher (50%), a working period of 1-5 years (31.4%) with a junior sales reps position. sales reps (42.19%). In 2019, 88,89% star performers came from PT. XYZ-1, the remaining 11,11% from PT. XYZ-2, while PT. XYZ 3 and 4 do not have star performers. Factors that affect star performers are competence (communication and adaptability), motivation (need for achievement, resilience) and superiors' support- coaching and mentoring, Teamwork, creativity, organizational culture and job autonomy do not have a significant effect on superior performing employees. Keywords: motivation, need for achievement, performance, relationships with superior, star performers